Augmenting Feeding Value of Rice Gluten Meal through Dietary Addition of Enzymes in Broilers - Dinani, O P; Tyagi, Pramod Kumar; Mandal, A. B.; Tyagi, Praveen Kumar; Dutta, Narayan (Indian Journal of Animal Nutrition, 2020)
A biological experiment of 42 days duration was undertaken to study the growth performance of broilers. A total of 384, day-old chicks were divided into 12 dietary treatments following 3x4 factorial design having 4 replicates per treatment with 8 birds in each. Twelve experimental diets were prepared by incorporating control, two different levels (15 and 17.5%) of rice gluten meal (RGM), and Â three different types of enzymes namely xylanase (X), protease (P) and multienzymes (M). Data pertaining to the growth performance of birds revealed no significant (P>0.05) difference in RGM levels (15 and 17.5%), but FCR was significantly (P<0.05) poor in 17.5% RGM level. Either of the three supplementations (X, P and M) significantly (P<0.05) improved the growth performance of the birds, best response being observed with protease supplementation. Thus, it may be concluded that protease supplementation may increase the effective and safe inclusion level of alternate protein source RGM from 15 to 17.5% for economic broiler production.